Communication studies, disciplination and the ontological stakes of interdisciplinarity: a critical review (Communication & Society, 2016)
Building on an in-depth analysis of the core literature grappling with the philosophical problematization of communication, this article examines the oft-asserted interdisciplinary nature of communication studies by assessing some of its underlying presuppositions at the ontological and epistemological levels. The article evaluates the coherence of our fragmented discipline through the articulation of the categories of the One and the Multiple in ontological and epistemological directions. In doing so, the recurrent conception of communication studies as an interdiscipline is criticized while recognizing the importance of undertaking interdisciplinary research within the field. Are especially considered the historical roots of interdisciplinary advocacies, namely the institutional demands for interdisciplinarity that have often resulted in conceptions of communication studies by communication scholars themselves as a crossroads or a service discipline. Building from Ernst Cassirer’s developments regarding the “theory of the concept’’, the author contends in the final section of the paper that the solution to the lack of coherence of the field lies in the necessity for communication studies to discipline themselves in order for the research undertaken within the field to acquire a common framework of intelligibility.